A review of aspirin resistance; definition, possible mechanisms, detection with platelet function tests, and its clinical outcomes - Pamukcu, Burak (Journal of thrombosis and thrombolysis, 2007)
Aspirin (acetylsalicylic acid) is one of the main therapeutics in prevention of thrombo-embolic vascular events. Its efficiency is proved in the prevention of cardiovascular events. However, antiplatelet effect of aspirin is not absolute in all patients and some patients experience thrombo-embolic events despite aspirin. These patients are clinically called as aspirin resistant or aspirin non-responders. Globally, a lot of people are affected by aspirin resistance according to the high prevalence of athero-thrombotic vascular diseases. A prevalence of 5.5-45% in patients with various cardiovascular disease by different laboratory methods has been reported for aspirin resistance. Clinical outcome of aspirin resistance has been demonstrated in patients with different vascular diseases. Detection of platelet function in patients treated with aspirin may be necessary in the prediction of clinical outcome. Point of care methods, which have correlated results with the standard light transmittance aggregometry may be appropriate choices in the detection of platelets' response to antiplatelet therapy. Adequate additional therapies may reduce atherothrombotic risks and major cardiovascular events rate in aspirin resistant subjects. None of the current researches advised the cessation of aspirin therapy. There is need to investigate the efficacy of additional adenosine diphosphate receptor antagonists or newer antiplatelet agents in aspirin resistant subjects. The intent of this paper is to review the literature discussing possible mechanisms, determination techniques, and clinical effects of aspirin resistance.